Lipoprotein apheresis in patients with peripheral artery disease and hyperlipoproteinemia(a). (May 2015) - Poller, Wolfram C.; Dreger, Henryk; Morgera, Stanislao; Berger, Axel; Flessenkämper, Ingo; Enke-Melzer, Kathrin
Abstract: Objective: Hyperlipoproteinemia(a) [Lp(a)-HLP] is a major risk factor for severe atherosclerosis. The present investigation sought to assess the effect of lipoprotein apheresis (LA) in patients with peripheral artery disease (PAD) and Lp(a)-HLP. Methods: In January 2013, we started a registry for Lp(a)-HLP patients who receive weekly LA in our center. So far, ten patients with severe PAD and isolated Lp(a)-HLP who recently underwent revascularization (index procedure) have been included. Pain level, ankle-brachial-index (ABI), transcutaneous oxygen pressure (tcpO2 ) and walking distance were determined before, as well as 1, 3, 6 and 12 months after initiation of LA. Furthermore, the mean time interval between revascularizations within the 12 months prior to the index procedure and up to 12 months after the index procedure was assessed. Results: All analyzed parameters significantly improved under LA. When comparing the results before LA with the results after 12 months, the ankle-brachial-index increased from 0.5 ± 0.2 to 0.9 ± 0.1 ( P < 0.001). The tcpO2 levels also increased from 42.9 ± 2.3 mmHg to 59.0 ± 8.9 mmHg ( P < 0.001). The improved microcirculation was associated with a reduction of the mean pain level from 7.0 ± 1.5 to 2.0 ± 0.8 ( P < 0.001) as determined using the visual analog scale. The walking distance increased from 87 ± 60 m to 313 ± 145 m ( P < 0.001). Importantly, the frequency of revascularization procedures was strongly decreased under LA. All patients combined underwent 35 revascularizations within the 12 months prior to the index procedure (mean interval between two revascularizations: 104.3 days). Since the index procedure, only one revascularization was necessary within 79 patient-months under LA (mean interval: 2404.5 days, P < 0.001). Conclusion: LA improves circulation, oxygen supply, level of pain and walking distance in patients with severe PAD and Lp(a)-HLP. The frequency of revascularization procedures is strongly reduced under LA treatment.